How to Teach Environmental Responsibility - A Pilot Study on Waste Management in Kindergarten Facilities - Joanna BARTNICKA; Peshraw MOHAMMED SULAIMAN (Communications of International Proceedings, 2021)
One of a major environmental challenge of  today's world with implications  for  human  health  and  well-being is waste management. In particular improper waste management is harmful to people causing air pollution, affecting water bodies or depletion of the ozone layer and eventually increasing the impact on climate change. human health environmental  preservation,  sustainability and  economy because of waste’s possible detrimental effect to human health and negative impact on global environment.  Taking this challenge as a background of the paper, a study was designed which aim was to develop a new approach to teach environmental responsibility. The main assumption of this approach is to include environmental awareness from the very beginning of children's education, starting with kindergarten. Composting in kindergarten facilities was the example of possible subject of lessons with the use of activating methods including kindergartners. Because the main condition of performing such lessons is to implement composting within kindergarten facilities, the pilot survey was conducted to find the status of the knowledge, ability and willingness of kindergarten managers in Poland to undertake composting deployment. The paper present the survey outcomes, where the main conclusion is that only few of the kindergartens use composting as a waste utilization method, managers’ knowledge about composting is mostly on average level and slightly over 40% of them are interested in changing the waste management towards implementing composting methods, giving the potential of launching the new learning opportunity for children to create new generations more environmentally friendly.
Keywords: Waste Management; Education; Activating Methods; Kindergarden.